A novelty pregnane C21-steroid from Cynanchum auriculatum. (December 2022) - Huang, Lie-jun; Fan, Yi-min; Jin, Jun; Yi, Ping; Gu, Wei; Jian, Jun-you; Yuan, Chun-mao; Hao, Xiao-jiang
Abstract: A novelty pregnane C21-steroid, cynansteroid F (1 ) and a new natural product 20-hydroxylatecaudatin (2 ), together with seven known compounds (3 –9 ) were isolated from the roots of Cynanchum auriculatum . The chemical structures were elucidated by analyses of physiochemical properties and 1D-NMR, 2D-NMR, HRESI-MS, IR and ECD spectral data. Among them, eight compounds (1 –4 and 6 –9 ) were firstly isolated from the roots of C. auriculatum . The chemotaxonomic analysis of these compounds was discussed. Graphical abstract: Image 1 Highlights: Nine compounds were isolated from the roots of Cynanchum auriculatum . Compound 1 was a novelty C21 -steroid, 2 was a new natural product. Compounds 3 –4, and 6 –9 were isolated from the roots of C. auriculatum for the first time. C21 -steroid can be recognized as typical biomarkers for the genus Cynanchum.